Déjà dit, jamais vu [rec. Philippe Lacoue-Labarthe: Typografie. Wybór, oprac. i wstęp Jakub Momro. Tłum. Jakub Momro i Andrzej Zawadzki. [Seria: Horyzonty Nowoczesności. T. 108]. Kraków: TAiWPN „Universitas”, 2014, ss. 372.] - Zając, Piotr (Śląskie Studia Polonistyczne, 2015)
The subject of the following review is the 2014 edition of collected articles and addresses of Philipe Lacoue-Labarthe entitled Typografie. A point of reference for his uniquely understood politicality and community (audience) is provided by the theses of a Czech philospher Jan Patočka. The following article emphasizes cohesion of Lacoue-Labarthe’s thought as seen in the volume in which the French philosopher discusses various texts in humanities, including literary, philosophical and musical. Typografie is presented as a significant voice in the ongoing debate about contemporary man.